Law and Urban Growth - ROBERT A. SILVERMAN (Princeton University Press, 2014)
"OF all the mysteries of legal history, perhaps the most impenetrable is the history of law in action, law as it was lived, not as it was supposed to be." Of all the mysteries of urban history, perhaps the least understood is the action of law in urban life.1 Trial courts were potentially important social institutions in the cities of late-nineteenth-century America. During the period 1880-1900, a watershed for the functioning of law, "new demands of desperate urgency were made on the administration of justice," placing novel stresses on trial courts. An increasing flow of immigrants from overseas and from the surrounding countryside combined with uncertain employment opportunities to burden urban communities with newcomers of little or no means. Such people found themselves entangled in wage disputes, landlord- tenant problems, and situations involving instruments of indebtedness. New technologies, especially in transportation and manufacturing, raised the standard of living but also injured and killed an increasing number. Within a generation, "the social importance of the law of torts (of injury)" had been transformed. Novel urban habits and practices demanded legal controls over the hazards created by crowded living.2 Trial courts were customarily divided into two major branches—criminal and civil—each having its own clerk and supporting staff but usually sharing the same judges. The criminal branch handled prosecutions involving wrongdoing that affected the public. The civil branch heard only those actions relating to the private rights of individuals, for example, those concerning debt or accidental injury.